MERETAS MAKNA KEBENARAN DALAM DISKURSUS FILOSOFIS (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
People’s thinking about their live have been often influenced by the doubt of something, in many ways, the feeling of doubtful will encourage someone to answer his doubts to the truth he believed. The truth means, the situation of no more the element of doubt and conflict that stimulate the unclearity . If there is something that is clearly uncontested and unrejected, then the truth has been reached. But it is very difficult to get a common understanding of the existing truth. From this case, emerged the various studies and theories that come one after another to explain the truth. There are many perspectives and rationale presented by the Eastern and western philosophers to explain the truth. The results of research done by philosophers have been formulated through their theories and thoughts based on realism andidealism, to the examination of the truth by using different approacesh such as correspondence, cohe-conference, and Hudhuri theories